Solar Energy for Traction of High Speed Rail Transportation: A Techno-economic Analysis - Nazir, Cawas Phiroze (Civil Engineering Journal, 2019)
To meet the growing expectation of traveling public, world railways are going ahead in a big way to introduce high speed trains Electric railways require huge amounts of energy. Many rail networks run their own dedicated power plants. With a view to augment the capacity of the rail networks grid connection so as to make the railway self-reliant, a grid tied PV solar plant with battery storage has been proposed. The present concept is based on installing solar panels along the length of a HS rail network so that the ballast-less tracks could be used as energy carriers. Ballast less tracks require little or no maintenance, and the space along the tracks provides a large surface area on which arrays of PV modules can be mounted to generate electricity from sunlight. An example demonstrates that a 330 MW grid connected PV solar plant with battery storage for the Mumbaiâ€“Ahmedabad high speed rail link, generates electricity at $1.67 Â 106 /MW output and levelized electricity cost at 12.05 c/kWh. Net saving in tariff after payback period is about $ 58 million per annum.